2015
DOI: 10.1007/s12012-015-9318-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Fas-Dependent and Mitochondria-Dependent Apoptotic Pathways in a Transgenic Mouse Model of Huntington’s Disease

Abstract: Huntington's disease is an autosomal dominant neurodegenerative disease caused by a CAG repeat expansion in the huntingtin gene. Heart disease is the second leading cause of death in patients with Huntington's disease. This study was to evaluate whether cardiac Fas-dependent and mitochondria-dependent apoptotic pathways are activated in transgenic mice with Huntington's disease. Sixteen Huntington's disease transgenic mice (HD) and sixteen wild-type (WT) littermates were studied at 10.5 weeks of age. The cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…These morphological changes may lead directly to cardiac energy metabolism imbalances. Indeed, a recent study suggested that cardiac Fas-dependent and mitochondria-dependent apoptotic pathways were activated in R6/2 hearts [38]. Mitochondrial structure disarrangement may thus result in an energy status imbalance in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These morphological changes may lead directly to cardiac energy metabolism imbalances. Indeed, a recent study suggested that cardiac Fas-dependent and mitochondria-dependent apoptotic pathways were activated in R6/2 hearts [38]. Mitochondrial structure disarrangement may thus result in an energy status imbalance in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Additional alterations in HD patients include subcellular abnormalities in fibroblasts, circadian dysfunction [2731], lymphocytes [32, 33], and erythrocytes [9]. Growing evidence now suggests that cells from cardiac and muscle tissues of HD patients bear aberrations related to the expression of mutant HTT [11, 1419, 3443]. Besides the cardiac abnormalities (described below), skeletal muscle dysfunction is very common in HD patients and leads to severe muscle wasting [11, 19].…”
Section: Peripheral Pathology Associated With Huntington’s Diseasementioning
confidence: 99%
“…Other studies have shown that expression of mutant HTT leads to intracellular aggregate formation in peripheral tissues and gene expression changes in HD peripheral tissues sections [10, 47]. Other abnormalities such as endocrine dysfunction, blood tissue abnormalities, and cell death in peripheral tissues have also been reported in both HD patients and animal models [11, 1419, 3443]. …”
Section: Peripheral Pathology Associated With Huntington’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The AKT family is an upstream factor of Bax and negatively regulates Bax expression. The function of Bax during ischemia has been well documented, and plays a crucial role in mitochondrial-dependent apoptosis (Bax, cytosolic Cyto C, activated caspase-9 and activated caspase-3) via inducing mitochondrial permeabilization and therefore the release of apoptogenic factors [25,36,37]. As shown in our data, significant increases of Bax protein abundance and disrupted MOMP are in accordance with elevated apoptotic rates observed in cardiomyocytes with AKT2 inhibition during ischemia, suggesting severe disruption of MOMP with additional AKT2 blockage.…”
Section: Discussionmentioning
confidence: 99%